Familial interstitial pneumonia in an adolescent boy with surfactant protein C gene (Y104H) mutation - Kuse, N.; Abe, S.; Hayashi, H.; Kamio, K.; Saito, Y.; Azuma, A.; Kudoh, S.; Kunugi, S.; Fukuda, Y.; Setoguchi, Y.; Gemma, A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Recent studies have suggested that some cases of familial interstitial pneumonia are associated with mutations in the gene encoding surfactant protein C (SFTPC). We report here a case of familial interstitial pneumonia in an adolescent boy whose paternal grandfather and father suffered from idiopathic interstitial pneumonia (IIP). The patient was asymptomatic but showed an abnormal shadow in the chest at his medical check-up. The surgical biopsy of the patient revealed non-specific interstitial pneumonia and showed pathological findings similar to those in his father’s autopsy.Genomic DNA from blood leucocytes of the patient was sequenced for the Thy104His (Y104H) SFTPC mutation. Based on these results, he was diagnosed with SFTPC mutation-associated familial interstitial pneumonia. There has been no clinical, physiologic and radiologic progression for 4 years since the diagnosis.The relation between clinical manifestation and the mutation site of the patient may broaden the spectrum of SFTPC mutation-associated interstitial pneumonia.